El Outsourcing Contable y su Influencia en los Costos Administrativos en las Empresas Ferreteras que están Obligadas a Llevar Contabilidad de la ciudad de Riobamba, 2022. - Yumi Pucha, Daniela Alexandra (2024)
ABSTRACT: This research was undertaken to address the challenges faced by hardware stores in Riobamba. These stores, due to economic limitations and a lack of specific accounting knowledge, often resort to accounting outsourcing to manage their financial needs and avoid sanctions. The primary objective of this study was to analyze the impact of this outsourcing on these companies' administrative costs in the year 2022. A representative sample of 35 companies was interviewed through an inductive method and a non-experimental qualitative research design, combining interviews and surveys to capture a comprehensive view of accounting practices and the economic impact of outsourcing. The findings suggest that, although many companies lean towards outsourcing and technological solutions, the effectiveness in cost reduction varies, highlighting the importance of tailoring these services to the specific needs of each company. The case study of “Ferretería Licán” serves as a compelling example, demonstrating a significant 32.62% reduction in administrative costs after implementing accounting outsourcing. This reduction, from USD 6.712 to USD 4.522 in just six months, underscores the potential of outsourcing to optimize financial management in the hardware sector of Riobamba. Moreover, the study reveals a notable decrease in accounting errors and fiscal penalties, further highlighting the effectiveness of outsourcing in improving accounting accuracy. These findings not only underscore the viability of accounting outsourcing as a strategy but also emphasize the need for a tailored approach for each company.